2012
DOI: 10.1016/j.chemosphere.2011.12.041
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of mesotrione-degrading bacteria from aquatic environments in Brazil

Abstract: Mesotrione is a benzoylcyclohexane-1,3-dione herbicide that inhibits 4-hydroxyphenyl pyruvate dioxygenase in target plants. Although it has been used since 2000, only a limited number of degrading microorganisms have been reported. Mesotrione-degrading bacteria were selected among strains isolated from Brazilian aquatic environments, located near corn fields treated with this herbicide. Pantoea ananatis was found to rapidly and completely degrade mesotrione. Mesotrione did not serve as a sole C, N, or S source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 27 publications
1
55
0
Order By: Relevance
“…Since mesotrione was marketed in 2003, few microorganisms have been reported to catabolize it (Durand et al, 2006;Batisson et al, 2009;Pileggi et al, 2012;Olchanheski et al, 2014). The detailed biodegradative pathway of mesotrione was only established with some of these microorganisms (Durand et al, 2010;Pileggi et al, 2012). Bacillus megaterium strain Mes11, isolated from soil, was able to completely and rapidly biotransform mesotrione leading to the accumulation of 2-amino-4-methylsulfonylbenzoic acid (AMBA) in the culture medium as the final product (Batisson et al, 2009).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Since mesotrione was marketed in 2003, few microorganisms have been reported to catabolize it (Durand et al, 2006;Batisson et al, 2009;Pileggi et al, 2012;Olchanheski et al, 2014). The detailed biodegradative pathway of mesotrione was only established with some of these microorganisms (Durand et al, 2010;Pileggi et al, 2012). Bacillus megaterium strain Mes11, isolated from soil, was able to completely and rapidly biotransform mesotrione leading to the accumulation of 2-amino-4-methylsulfonylbenzoic acid (AMBA) in the culture medium as the final product (Batisson et al, 2009).…”
Section: Introductionmentioning
confidence: 97%
“…Mesotrione, chemically derived from a natural phytotoxin produced by the bottlebrush plant Callistemon citrinus (Mitchell et al, 2001), was developed to minimize adverse effects on the environment. Since mesotrione was marketed in 2003, few microorganisms have been reported to catabolize it (Durand et al, 2006;Batisson et al, 2009;Pileggi et al, 2012;Olchanheski et al, 2014). The detailed biodegradative pathway of mesotrione was only established with some of these microorganisms (Durand et al, 2010;Pileggi et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…23 The herbicide mesotrione is an agrochemical that inhibits the HPPD enzyme in plants. 20 The conventional methods for detecting and quantifying mesotrione are usually liquid chromatography coupled with UV spectroscopy, 24 mass spectrometry, 25 tandem mass spectrometry, 26 or°uorescence spectroscopy. 27 The high sensitivity of such methods, with detection limits at the level of nanograms per liter, 28 can be compared to the sensitivity of the cantilever described in this study, which detected target molecules at the level of nanograms per mL.…”
Section: Introductionmentioning
confidence: 99%
“…125) A similar reduction was reported for the degradation of dichloran (5) 59) and mesotrione (58). 86) Although metabolites were not identified, (42) and disulfoton (48) were biodegraded by many kinds of bacteria isolated from ponds. 43) Amides, ureas and carbamates are either hydrolyzed 62,126,127) or oxidized 128,129) during their microbial degradation.…”
Section: Transformation By Enriched Community or Isolated Microbesmentioning
confidence: 83%
“…84) Novick and Alexander 85) reported a doubled yield of products through the incubation of propachlor (33) in eutrophic lake water by addition of glucose, but no microbes using (33) as carbon and energy sources could be isolated. Recently, Pileggi et al 86) isolated Pantoea ananatis from Brazilian freshwater and showed its co-metabolic activity on mesotrione (58) by varying the nutrient composition of the medium. The mineralization of propham (20) in lake water was enhanced by ca.…”
Section: Co-metabolismmentioning
confidence: 99%